2020
DOI: 10.1128/mra.01441-19
|View full text |Cite
|
Sign up to set email alerts
|

Draft Genome Sequence of Streptomyces sp. Strain C8S0, Isolated from a Highly Oligotrophic Sediment

Abstract: Streptomyces spp. are prolific bacteria producing bioactive metabolites. We present the draft genome sequence of Streptomyces sp. strain C8S0, which was isolated from a highly oligotrophic sediment from the Cuatro Cienegas Basin (Mexico). The whole-genome assembly comprised 6,898,902 bp, with 18 biosynthetic gene clusters, including those for nonconventional terpenes, nonribosomal peptides, and polyketides.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…The soils of the Cuatro Cienegas Basin are characterized by a extremely unbalanced N:P (157 : 1) soil stoichiometry, and rich sulfur, magnesium and calcium sulfate concentrations [71]. It has previously been shown that these conditions conserve a great diversity of endemic microbes with novel biosynthetic potential [32, 72]. For instance, our research group has previously described new diversity in desferrioxamine siderophores (propionyl-ferrioxamine, m / z =628.17; aryl-ferrioxamine, m / z =690.26) in species of Microbacterium , Micrococcus and Streptomyces [33].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The soils of the Cuatro Cienegas Basin are characterized by a extremely unbalanced N:P (157 : 1) soil stoichiometry, and rich sulfur, magnesium and calcium sulfate concentrations [71]. It has previously been shown that these conditions conserve a great diversity of endemic microbes with novel biosynthetic potential [32, 72]. For instance, our research group has previously described new diversity in desferrioxamine siderophores (propionyl-ferrioxamine, m / z =628.17; aryl-ferrioxamine, m / z =690.26) in species of Microbacterium , Micrococcus and Streptomyces [33].…”
Section: Discussionmentioning
confidence: 99%
“…CC55 and Actinokineospora sp. PR83 were isolated from the Cuatro Cienegas Basin, as previously reported [ 32 ]. Lentzea sp.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…23 Environmental strains were isolated from Cuatro Cienegas Basin, and eight strains from Calakmul in Mexico. Genome sequences were obtained using methods previously reported (Gallegos-Lopez et al, 2020). On the other hand, nine genomes of strains isolated from various locations in Chile (4 from Valparaiso, 4 from Comau Fjord, Huinay and 1 from Penas Gulf) were also included.…”
Section: Genome Sequencesmentioning
confidence: 99%